Outcomes of routine surgical exploration in children who admitted to the emergency service with acute scrotum - Sancar, Serpil; Ozcakir, Esra; Kaya, Mete (The European Research Journal, 2017)
Objectives. The acute scrotum frequently presents a diagnostic and therapeutic challenge. In cases where the testicular torsion cannot be excluded, a surgical exploration is recommended. The aim of the study was to present the results of our management in the patients with acute scrotum. Methods. We reviewed the medical records of 33 patients suffering from acute scrotal pain underwent scrotal exploration between 2011 and 2016. Anamnestic data (age of patient, duration of anamnesis prior to admission and the side that was involved), scrotal color Doppler ultrasound (SCDUS) results, intraoperative findings, mode of operative treatment, and the clinical outcomes were analyzed. Results. Patients aged from several hours up to 17 years of age (average 11.9 years). The duration of symptoms prior to admission ranged from 3 h to 4 days, (average 32 h). Acute scrotum was found 18 in right side, 15 in left side. SCDUS was diagnostic for testicular pathologies in 19 (51%) of 30 patients. In patients who underwent scrotal exploration, 18 (54%) had a testicular torsion, 11 (33%) had a torsion of the appendix testis, and 4 (12%) had an orchio-epididymitis. Three patients who found testicular torsion required an orchidectomy immediately because of necrosis. The rest had detorsion and ipsilateral fixation of testis. Three patients underwent second look, and orchiectomy was performed in 2 of them. In 2 of detorsioned testes, two testicular atrophies developed on follow-up period. Conclusion. Regardless of the etiology, the management of the patients with acute scrotum by urgent surgical intervention allows the salvage of a possible testicular torsion.